Plasma-derived exosomal let-7c-5p, miR-335–3p, and miR-652–3p as potential diagnostic biomarkers for stable coronary artery disease - Han, Jian; Cui, Xiaogang; Yuan, Tianqi; Yang, Zhiming; Liu, Yue; Ren, Yajuan; Wu, Changxin; Bian, Yunfei (Frontiers in Physiology, 2023)
Objectives: Circulating exosomal microRNAs (miRNAs) have been identified as promising biomarkers for diagnosis of cardiovascular diseases. Nevertheless, the diagnostic potential of miRNAs in circulating exosomes for stable coronary artery disease (SCAD) remains unclear. We aim here to analyze the exosomal differentially expressed miRNAs (DEmiRNAs) in plasma of SCAD patients and investigate their diagnostic potential as SCAD biomarkers. Methods: Plasma was collected from SCAD patients and healthy controls, and exosomes were isolated by ultracentrifugation. Exosomal DEmiRNAs were analyzed by small RNA sequencing and were further validated by quantitative real-time PCR (qRT-PCR) in a larger set of plasma samples. Relationships between plasma exosomal let-7c-5p, miR-335-3p, miR-652-3p, genders and Gensini Scores in patients with SCAD were analyzed using correlation analyses. Moreover, we conducted receiver operating characteristic (ROC) curves for these DEmiRNAs and analyzed their possible functions and signaling pathways. Results: Vesicles isolated from plasma displayed all characteristics of exosomes. In the small RNA sequencing study, a total of 12 DEmiRNAs were identified, among which seven were verified to be statistically significant by qRT-PCR. The areas under the ROC curves of exosomal let-7c-5p, miR-335-3p, and miR-652-3p were 0.8472, 0.8029, and 0.8009, respectively. Exosomal miR-335-3p levels were positively correlated with Gensini scores of patients with SCAD. Bioinformatics analysis revealed that these DEmiRNAs may be involved in the pathogenesis of SCAD. Conclusion: Our findings indicated that plasma exosomal let-7c-5p, miR-335-3p, and miR-652-3p can be used as promising biomarkers for diagnosis of SCAD. In addition, plasma exosomal miR-335-3p levels were positively correlated with the severity of SCAD.